Sistem Pendukung Keputusan Pemilihan Supplier Air Bersih Tangki Depot Galon Berbasis Web Menggunakan Metode Simple Additive Weighting (SAW) Pada Depot Aiba - Surya Kencana, Bayu (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The analysis and design of this decision support system aims to address issues surrounding the selection of the best supplier which is a problem at Aiba Depot. Supplier selection is one of the important things in purchasing activities for entrepreneurs, where purchasing activities are activities that have important value for business actors because purchasing components, raw materials and supplies represent a sizable portion of the finished product. In making decisions to select suppliers, decision makers need analytical tools that enable them to solve complex problems so that the decisions taken are of a higher quality. In making this decision using the Simple Additive Weighting (SAW) method. Selection of criteria that will influence that is in terms of price, delivery timeliness, quality of goods and service. This research will be a case, namely by looking for alternatives based on predetermined criteria, to find a weight in each attribute. Then a ranking process is carried out which will determine the alternative,namely the best supplier.